Pengembangan Perangkat Pembelajaran Terpadu Model Webbed Melalui Pendekatan Tematik Di TK - Rosnawati Rosnawati; Tanjung Nia Sari (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2021)
The objectives of this study include: (1) to find out how a thematic approach is used in the development of integrated learning using the webbed model, which focus on the concept of learning by doing in kindergarten; (2) to determine the effectiveness of the web-based integrated learning model using a thematic approach that focus on the concept of learning through early childhood learning; (3) to create a valid Webbeb learning model using the learning-by-doing concept. The method in this study is a research and development approach. The results of this study include: (1) the development of this teaching tool is based on research and development theory that focuses on creating a teaching device so that learning is not monotonous, draws children’s attention to learning, so that learning is more meaningful, because children are more proactive in problem solving using their real experiences; (2) Webbeb learning model, based on a thematic approach through a learning-by-doing concept, is effective for classroom learning because it focuses on learners so that learners find their own material concepts by focusing on the school environment; and (3) a web-integrated learning model using a thematic approach through a learning-by-doing concept that was created after validation by a multi-custom validator. Keywords: :Learning device, webbed, learning by doing References Depdiknas. (2006). Permendiknas No.22 Tahun 2006 Tentang Standar Isi Jakarta: Depdiknas. Global Shadows: Africa in the Neoliberal World Order. Dimyanti & Mudjiono. (2013). Belajar&Pembelajaran. In belajar&pembelajaran. Fathurohman, O. (2017). Hakikat Bermain Dan Permainan Anak Usia Dini Di Pendidikan Anak Usia Dini (PAUD). As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 2(1), 27–36. Fatihah, N., & Difla Nadjih. (2017). Hubungan Pendidik Dan Terdidik Dalam Al-Quran. Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 7(2), 73–86. Fitriyani, F. N. (2017). Perkembangan Bermain Anak Usia Dini. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(2), 29–44. Hardiyanti, W. E., Ilham, M., Suziman, A., & Astriyani, A. (2020). PENGGUNAAN EMOJI UNTUK MENINGKATKAN PERILAKU BAIK (WELL-BEING) DAN KEMAMPUAN BAHASA ANAK USIA DINI. EARLY CHILDHOOD : JURNAL PENDIDIKAN. https://doi.org/10.35568/earlychildhood.v3i2.653 Hasbullah, H. (2016). Model Pengembangan Kurikulum PAUD. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 1(1), 21–28. Huliyah, M. (2016). Pengembangan Daya Seni Pada Anak Usia Dini. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(2), 149–164. Imroatun, I. (2014). Permainan Tradisional Sebagai Pembelajaran Kecakapan Sosial Bagi Anak Usia Dini. Jurnal Sains Psikologi, 3(1), 1–11. Mawaddah, S., & Maryanti, R. (2016). Kemampuan Pemahaman Konsep Matematis Siswa SMP dalam Pembelajaran Menggunakan Model Penemuan Terbimbing (Discovery Learning). EDU-MAT: Jurnal Pendidikan Matematika. https://doi.org/10.20527/edumat.v4i1.2292 Nuryati. (2016). Pengembangan Kompetensi Profesional Guru Pendidikan Anak Usia Dini Melalui Pemberdayaan Organisasi Himpaudi Di Kecamatan Serang. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 1(2), 165–176. Nuryati, N. (2017). Perkembangan intelektual pada anak usia dini. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(2), 59–78. Prihantoro, A. (2021). Asesmen Formatif Pada Pendidikan Anak Usia Dini Di Indonesia. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 6(1), 53–64. https://doi.org/10.32678/AS-SIBYAN.V6I1.3955 Sarumaha, Y. A. (2016). Perubahan Pembelajaran Yang Berpusat Pada Guru Ke Berpusat Pada Siswa. Intersections, 1(1). Sholahudin, M. (2013). EVALUASI KINERJA GURU (Manajemen Evaluasi Peningkatan Profesionalitas Guru). Tafaqquh: Jurnal Penelitian dan Kajian Keislaman. Sugiono, P. D. (2014). Metode penelitian pendidikan pendekatan kuantitatif.pdf. In Metode Penelitian Pendidikan Pendekatan Kuantitatif, Kualitatif Dan R&D. Trianto. (2007). Model Pembelajaran Terpadu dalam Teori dan Praktek. Jakarta, Prestasi Pustaka.